Entrepreneurial competencies and SMEs’ growth: the mediating role of network competence - Tehseen, Shehnaz *; Ahmed, F. U.; Qureshi, Zuhaib Hassan; Uddin, Mohammad Jasim *; Ramayah, T (Emerald, 2019)
Purpose The purpose of this paper is twofold. First, to examine the influence of two dimensions of entrepreneurial competencies, namely, strategic competency and ethical competency on the growth of small and medium enterprises (SMEs); and second, to explore the role of network competence as a mediator among these understudied variables. Design/methodology/approach: The data for this study were collected from wholesale and retail-based SMEs in Malaysia through a standard structured questionnaire. PLS–SEM approach was utilised to analyse the data. Findings: Although the findings did not reveal a direct effect of strategic and ethical competencies of entrepreneurs on SMEs’ growth, these competences, however, were found to be influential in driving their growth when network competence was used as a mediator. Originality/value: The existence of a mediation effect between strategic and ethical competencies and SMEs’ growth via network competence has provided insights which add new knowledge to the extant entrepreneurship and SMEs’ performance literature.